The Role of Postal Networks in Expanding Access to Financial Services : Egypt's Postal Finance Services - World Bank (Washington, DC, 2013)
This paper discusses the role of the postal network in expanding access to financial services in Egypt. It reviews the public postal operator within the postal sector and within the broader context of the communications sector. The roles of the postal network and state and privately-owned banks are also reviewed from the perspective of the financial sector development, with particular focus on payments systems development and microfinance. The ultimate goal of postal reform is to create a system where modern technology and a free flow of information benefit the customer. A modern, efficient postal service that utilizes the latest information technology will not only increase Egypt's social and economic development, but will also contribute significantly to the creation of an Egyptian information society.